COMPARATIVE ANALYSIS OF STRAINS GROWING PLEUROTUS OSTREATUS AND PLEUROTUS ENRIGII - Bazán G., Dora (2004)
This paper describes the cultivation of two Pleurotus' mush-rooms. The parameters about control growth of mush-rooms are reported.